Multi-Device Classification Model for Game Interaction Techniques. Issue 8 (3rd August 2018) - Breyer, Felipe; Kelner, Judith; Clua, Esteban
ABSTRACT: The player should enjoy games through the game controller of their preference and keep the best possible game experience regardless their option. This article proposes a novel classification model for game interaction techniques from the player perspective and with direct control of a single humanoid avatar based on three characteristics: Effort, Duration, and Context. Combining the three characteristics, we classify the game interaction techniques into nine isomorphic categories. We conducted three experiments. The first ( N = 57) and second ( N = 45) were a paired quantitative comparison evaluation method, allowing the volunteer to play the same game level twice, changing only the interaction technique for one action. This aimed at validating our initial proposal with users. The third ( N = 100) was also a comparative test. The volunteer played the same stage twice using the button-interaction based version as a reference against one of another four device-based versions. The goal was to extend the proposed classification model to other interaction devices to check if the interaction metaphor was kept coherent. In all three experiments, we chose the 202 participants as a convenience sample. The users' experiments support all the research hypotheses. We conclude that, if our proposed guideline with our interaction technique classification model is applied, it may expect a positive impact on the players' experiences.